Implementation of Sharia Production Principles in the Production Process of Character Chocolate - Toyibatussalamah Toyibatussalamah; Isma Nurrokhim; Ali Mahmud (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2025)
The Sincan Coklat Home Industry is a home-based industry that produces character chocolate snacks. Sharia-compliant production principles emphasize not only efficiency and profitability but also the values ​​of halal certification, fairness, and social responsibility throughout the production process. The researcher aims to examine how the principles of sharia production, as proposed by Yusuf Qardhawi, can be practically implemented in the character chocolate manufacturing process within the Sincan Coklat home industry. This research employed a qualitative, conceptual, and descriptive approach, examining production practices in the field and linking them to Yusuf Qardhawi's theory of sharia economic production. This study shows that the Sincan Coklat home industry produces two products: jar chocolate and stick chocolate. The Sincan Coklat home industry has endeavored to implement sharia principles such as selecting halal raw materials, implementing a clean and safe production process, fair labor management, and avoiding practices containing elements of gharar, riba, and dharar. However, management improvements and halal certification are still needed to strengthen consumer trust. Thus, this research contributes to the development of the concept of halal production based on sharia values ​​in the home industry sector, in line with Yuuf Qardhawi's view of Islamic economics which is oriented towards welfare and blessings.